Divanü Lügati't-Türk'teki Şiirlerde İsim Hal Eklerinin Kullanılışları - Başdaş, Cahit (İlim Yayma Cemiyeti, 2001)
The author firstly elaborates on the case category in Turkish and then deseribes the manners they are employed in. He also indicates historical changes in the structures and functions of case suffixes. In doing this, he includes samples taken from DLT and comes to a conclusion indicating that no major differences appear in the usages and functions the case suffixes between DLT and other Turkish words inthe same period.
Usages of Case Suffixes in the Poems in Divanü Lugati 't-Türk (DLT)
Keywords: Divanü Lugati't-Turk; Case Suffixes; Turkish; Old Turkish; Morphology